Survey on integration of cloud computing and WSN to identify best Cloud service provider - M, Ms.Vedambika; Rani S, Ms. Soja (IJRDO -Journal of Computer Science Engineering, 2016)
ireless Sensor Networks are used to sense the environment conditions and collectthe information. The collected information is stored in the cloud in which the user can accessthe required information. The integration of both cloud service provider and sensor networkprovider will provide the effective service to the cloud service user. This paper is a generalsurvey of all the sensor network provider and cloud service provider integration. The majorityof the survey is mainly focused on the authenticated trust and reputation calculation forsensor network provider and cloud service provider